44.1k views
5 votes
HELP I DON'T UNDERSTAND

HELP I DON'T UNDERSTAND-example-1

1 Answer

3 votes
x^2 - 12x = 61
Take half of the coefficient of the middle term (half of -12x), square this result, and then add, and then subtract, from -12x:

x^2 - 12x + (6)^2 - (6)^2 = 61

(x-6)^2 - 36 = 61, and so (x-6)^2 = 97

Note: These results are all equivalent; choose the one you think best.
User Takje
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.